The vulnerability of a centralized food system: An opportunity to improve food security in times of COVID-19-Peru perspective - Tirado-Kulieva, Vicente Amirpasha; Miranda-Zamora, William Rolando; Hernández-Martínez, Ernesto; Choque-Rivera, Tania Jakeline; Luque-Vilca, Olivia Magaly (Frontiers in Sustainable Food Systems, 2022)
COVID-19 has had a strong impact on the food supply chain (FSC) in many countries. The objective of this study was to determine the vulnerability of the FSC in a developing country, namely Peru. The main weakness of the FSC is its centralization, and COVID-19 aggravated this deficit in Peru. This prevents its stability on a large scale, especially in rural areas, which suffer from food and nutritional insecurity. In spite of this, the food system was stabilized due to agricultural, livestock and fishing potential of Peru. In addition, the efforts of local producers and informal vendors helped to maintain the availability of food throughout the country. Several examples of short (and decentralized) FSC were described, highlighting their importance for supplying the population in different areas of the country. In addition, they allow for rapid resolution of interruptions such as the current health crisis. Also mentioned are some suggestions for strengthening Peru's FSC such as the use of new technologies, self-production of food and the exploitation of non-conventional food sources. Emphasis is placed on the importance of environmental sustainability of the FSC and of implementing strategies to prevent illness among workers. This study aims to reflect on the importance of having a resilient and flexible FSC. Taking Peru as a model, the information provided is useful to understand how to improve the food system through the intervention of all the agents involved, such as government, academia, industry and the population.